2008
DOI: 10.1007/s11064-008-9826-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Mechanism of the Up-Regulation of Fibrinolytic Activity in Painful Peripheral Nerve Injury

Abstract: Peripheral nerve injury is followed by Wallerians degeneration (WD) and degradation and regeneration of the extracellular matrix (ECM) are very important events in these processes. We tested fibrinolytic activities and the expression level of tPA and uPA levels in chronic constriction injury (CCI) model. The presented data demonstrates that in the injury nerve of CCI model, the fibrinolytic activities is upregulated and main caused by the upregulation of tPA expression. We also find that the activities of tPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…While several of these clinical conditions are characterized by acute or chronic pain [e.g., inflamed tissues (Lee et al, 2013; Alkhatib et al, 2014) or nerve injury (Sugimoto et al, 2008; Tsuda et al, 2008; Yong and Guoping, 2009; Tsuda et al, 2013)], the role of the ECM in the associated pain syndromes remains poorly understood. We have previously shown that versican, a large chondroitin sulfate proteoglycan ECM molecule that labels the non-peptidergic, isolectin B4 staining (IB4+) population of nociceptors helps to determine the function of these nociceptors (Bogen et al, 2005; Bogen et al, 2015).…”
mentioning
confidence: 99%
“…While several of these clinical conditions are characterized by acute or chronic pain [e.g., inflamed tissues (Lee et al, 2013; Alkhatib et al, 2014) or nerve injury (Sugimoto et al, 2008; Tsuda et al, 2008; Yong and Guoping, 2009; Tsuda et al, 2013)], the role of the ECM in the associated pain syndromes remains poorly understood. We have previously shown that versican, a large chondroitin sulfate proteoglycan ECM molecule that labels the non-peptidergic, isolectin B4 staining (IB4+) population of nociceptors helps to determine the function of these nociceptors (Bogen et al, 2005; Bogen et al, 2015).…”
mentioning
confidence: 99%
“…The implementation of these components into a nerve conduit delivery system will enable a degree of control over the length and processes of the Wallerian degeneration phase [14, 24, 63]. Wallerian degeneration is a term describing the rapid breakdown of axons and myelin sheaths after injury to neural tissues (Figure 3) [64]. Although it is a process triggered for the creation of a microenvironment supportive for nerve regeneration, it additionally initiates the onset of inflammation and intensification of pain [9, 24, 45, 6568].…”
Section: Requirements For Optimal Peripheral Nerve Regenerationmentioning
confidence: 99%